Sexual Victimization and Mental Health in Female University Students - Blanco, Vanessa (Journal of interpersonal violence, 2022)
Although sexual assaults on female university students are a public health concern, studies that have examined this issue have not used behaviorally specific definitions of the various types of sexual victimization. Furthermore, hardly any data exists on female Spanish university students. The objectives of this study were to analyze the prevalence of different forms of sexual assault against female Spanish university students, determine the risk factors associated with sexual assault, analyze the association between sexual victimization and mental health problems, and determine the differential risk of more serious types of sexual assault. A cross-sectional study was conducted among a random sample of 871 students from the University of Santiago de Compostela (Spain) (mean age 20.7 years, SD = 2.8). The current study assessed various types of sexual violence (i.e., unwanted sexual contact, attempted coercion, coercion, attempted rape, rape), as well as rates of depression, anxiety, stress, eating disorders, substance abuse, suicide risk, and suicide attempts. Of the female students surveyed, 28.5% had suffered some form of sexual violence during the previous year, 22.3% reported unwanted sexual contact, 8.8% attempted coercion, 6.5% coercion, 10.4% attempted rape, and 7.9% had been raped. Lower risk was associated with having a partner and being heterosexual. Being 18 years of age and prior experiences of sexual victimization were associated with higher risk. Being the victim of attempted coercion was associated with a higher risk of depression, while victims of attempted rape were at higher risk for substance use. Rape victims were at the highest risk for all mental health conditions studied, with the exception of suicide attempts. Due to the high rates at which Spanish female university students experience sexual violence, planning and resources are needed to address their mental health needs, especially those who are victims of rape.